FAKTOR-FAKTOR PENENTU KEPUTUSAN PEMBELIAN MELALUI E-COMMERCE PAD PT. GRE - Yuniarty Yuniarty; Bahtiar S. Abbas (Jurnal Manajemen Indonesia, 2018)
This study aimed to determine the factors that influence purchasing decisions through e-commerce on PT. GRE. The reasearch was conducted to determine whether there is influence of information quality, company reputation, appearance of the site, the benefits received from online shopping, trust, experience shopping through e-commerce, and demographic characteristics to the purchasing decisions through e-commerce. This study took a sample of 96 customers of package tours at PT. GRE that ever make transactions through e-commerce site at least one time. The method of analysis used to test the influencing is binary logistic regression after tested the validity and reliability and confirmatory factor analysis. The results showed that the information quality, the reputation of the company, the benefit received from online shopping, trust, and experience shopping through e-commerce, has a significant influence on the decision to buy through e-commerce at PT. GRE. PT. GRE as the e-commerce businesses are expected to pay more attention to these factors in attracting more customers to make purchases through the e-commerce. Information quality is the factor that most influences buying decisions through e-commerce at PT. GRE and appearance of the site, age, and gender had no significant influence on purchase decisions through e-commerce. PT. GRE can also focus on improving the quality of information in the website. Keywords—Purchase Decision; E-commerce; Binary Logistic Regression Abstrak Penelitian ini bertujuan menentukan faktor yang berpengaruh terhadap keputusan pembelian melalui ecommerce pada PT. GRE. Pengujian dilakukan untuk mengetahui ada tidaknya pengaruh kualitas informasi, reputasi perusahaan, tampilan situs, keuntungan yang diterima dari belanja online, kepercayaan, pengalaman belanja melalui e-commerce, dan karakteristik demografi terhadap keputusan membeli melalui e-commerce. Penelitian ini mengambil sampel sebanyak 96 pelanggan paket tur PT. GRE yang setidaknya satu kali pernah melakukan transaksi melalui situs e-commerce. Metode analisis yang digunakan untuk menguji pengaruh ini adalah regresi logistik binari. Hasil penelitian menunjukkan bahwa kualitas informasi, reputasi perusahaan, keuntungan yang diterima dari belanja online, kepercayaan, dan pengalaman belanja melalui e-commerce, berpengaruh signifikan terhadap keputusan membeli melalui e-commerce PT. GRE. PT. GRE sebagai pelakuecommerce diharapkan untuk lebih memperhatikan faktor-faktor tersebut dalam menarik lebih banyak pelanggan untuk melakukan pembelian melalui e-commerce. Kualitas informasi merupakan faktor yang paling mempengaruhi keputusan membeli melalui e-commerce pada PT. GRE dan tampilan situs, usia, dan genderberpengaruh tidak signifikan pada keputusan membeli melalui e-commerce. PT. GRE juga dapat menfokuskan peningkatan kualitas informasi dalam website. Kata kunci—Keputusan Pembelian; E-commerce; Regresi Logistik Binari